Effects of temperament on physiological, productive, and reproductive responses in Bos indicus beef cows - Cooke, R. F. [UNESP] (2017)
This experiment evaluated the effects of temperament on physiological, productive, and reproductive responses in Bos indicus beef cows. A total of 953 lactating, multiparous, non-pregnant Nelore cows (age = 99 +/- 2 mo; days post-partum = 51.4 +/- 0.3 d; BCS = 5.34 +/- 0.04; BW = 430 +/- 2 kg) were allocated into 8 groups of approximately 120 cows each. Groups were assigned to an estrus synchronization + timed-AI protocol at the beginning of the breeding season. Concurrently with AI, blood samples were collected, hair samples were clipped from the tail switch, and cow temperament was evaluated via chute score and exit velocity. Individual exit score was calculated within each group by dividing exit velocity into quintiles and assigning cows with a score from 1 to 5 (1 = slowest; 5 = fastest cow). Temperament scores were calculated by averaging cow chute score and exit score, and used to define cow temperament (<= 3 = adequate, n = 726; ADQ; > 3 = excitable, n = 227; EXC). Cows not pregnant to AI were assigned to a second timed-AI protocol (n = 184 ADQ and 72 EXC) or exposed (n = 269 ADQ and 90 EXC) to bulls for 60 d. Pregnancy status was verified 30 d after each AI and 45 d after the breeding season via transrectal ultrasound. Cow age, BW, BCS, and d post-partum at the beginning of the breeding season were similar (P >= 0.27) between ADQ and EXC cows. At first timed-AI, EXC had greater (P < 0.01) serum cortisol but similar (P >= 0.87) serum haptoglobin and hair cortisol concentrations compared with ADQ cows (49.1 vs. 39.1 ng/mL of serum cortisol, SEM = 1.0). Pregnancy rate to first timed-AI tended (P = 0.09) to be less in EXC vs. ADQ cows (41.0 vs. 47.3%; SEM = 3.6), whereas no treatment differences were detected (P >= 0.23) for subsequent pregnancy outcomes. Calving rate was less (P = 0.04) in EXC vs. ADQ cows (68.3 vs. 74.8%; SEM = 2.2), which can be attributed to the greater (P = 0.05) pregnancy loss detected in EXC cows (9.9 vs. 5.9%; SEM = 1.4). Weaning rate tended (P = 0.09) to be less, whereas calf weaning BW and age were less (P = 0.05) in EXC vs. ADQ cows (63.9 vs. 69.4%, SEM = 2.4; 209 vs. 212 d, SEM = 1; 204 vs. 210 kg, SEM = 2). Hence, kg of calf weaned/cow exposed to breeding was reduced (P = 0.04) in EXC vs. ADQ cows (130 vs. 146 kg, SEM = 5). In summary, B. indicus cows with excitable temperament had reduced reproductive performance and overall productivity compared to cohorts with adequate temperament when exposed to timed-AI + natural breeding.